Condition for intersection occupation measure to be absolutely continuous - Chen, X. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 519.21 Given the i.i.d. R^d-valued stochastic processes X_1(t),…, X_p(t), p2, with the stationary increments, a minimal condition is provided for the occupation measure μ_t(B)=_[0,t]^p1_B(X_1(s_1) - X_2(s_2),…, X_p-1(s_p-1) - - X_p(s_p))ds_1… ds_p,BR^d(p-1), to be absolutely continuous with respect to the Lebesgue measure on R^d(p-1). An isometry identity related to the resulting density (known as intersection local time) is also established.